Implantação do controlador preditivo multivariável DMC em uma planta piloto - Pereira, Rogério Passos do Amaral (2011)
This work aims to implement the predictive multivariable DMC controller in a real plant and compare it with the multi-loop PID. The practical application is made in a pilot plant located in the IFES / Serra, where pressure and level are controlled with the speed of the pump and the valve opening. The process model, the calculation of the relative gain array to determine the degree of coupling of the loops and the tuning of the multi-loop PID controllers are presented. The initial tuning of the PID is suggested by a simulator that compares the performance of various tuning methods commonly found in the literature. The initial DMC tuning is suggested by a simulator based on genetic algorithm. In both cases the final tuning is adjusted manually to improve the performance of the loops. Plant responses to step using the multi-loop PID and DMC are compared with and without restrictions on the valve opening and the pump speed. A didactic interface developed with the LabVIEW software is used to interact with MATLAB and the CompactRIO controller, this iteration allows use MATLAB optimization functions in the implementation of the DMC controller.